EPIDEMIOLOGY OF SCHISTOSOMIASIS IN BUFFALOES UNDER DIFFERENT MANAGEMENTAL CONDITIONS IN FOUR DISTRICT OF PUNJAB, PAKISTAN - G. M. Arshad; A. Maqbool; M. F. Qamar; S. M. H Bukhari; H. A. Hashmi; M. Ashraf (Journal of Animal and Plant Sciences, 2011)
The study was conducted to record the prevalence of Schistosomiasisin buffaloes in four districts of the Punjab, i.e., Lahore, Sargodha, Kasur and Sheikhupura. Overall prevalence of Schistosomiasis in different managemental conditions in farms of Punjab province indicated that infection was the highest (17%) in Kasur district followed by Sheikhupura (14.83), then Lahore (14.6%) and the lowest (13.66%) in Sargodha. The highest month wise prevalence was recorded during August (25.5%) followed by July whereas the lowest during December and January. Infection in buffaloes was higher in animals over two years of age (19%) than animals below two years of age (5%) in all the four districts of Punjab. The prevalence was higher in females (15.98%) than male (9.48%). There is variation in the prevalence as there is difference in the environmental and managemental condition of the area.
Keywords: Epidemiology; Schistosomiasis; Buffaloes; Punjab; Pakistan.